STUDY OF EPIDEMIOLOGICAL ASPECTS OF SYPHILIS IN PREGNANT WOMEN IN THE STATE OF TOCANTINS - Brito Gonçalves, Caio Willer (2020)
Syphilis is a systemic infectious disease caused by the spirochete Treponema pallidum, during pregnancy, if not treated properly, syphilis results in early fetal and neonatal deaths. This study aimed to assess the epidemiological aspects of the incidence of gestational syphilis in the state of Tocantins. A cross-sectional, retrospective study with a quantitative and analytical approach was carried out by consulting the Ministry of Health's (MS) Health Information System (SINAN) database from January 2009 to December 2018. 2182 cases of syphilis were diagnosed in the studied period, the most prevalent age group was 20 to 29 years of age, totaling 52.7% of cases. There was a higher prevalence among incomplete 5th to 8th grade pregnant women, with 456 cases and with regard to clinical classification, the highest prevalence was primary syphilis, 43.3% of the total cases. The data presented in this study confirm that gestational syphilis in the state of Tocantins is still on the rise, thus generating questions related to prenatal care.